Prevalence of Benign Prostatic Hyperplasia and Prostate Cancer Among Adults in Pakistan - Muhammad, Raza; Bhatti, Muhammad Shahid; Khan, Muhammad Saif Ullah; Faisal; Ali, Sameer; Bokhari, Noreen Maqbool; Mehtab, Ghazal; Ahmad, Irshad; Ali, Jamshid (Indus Journal of Bioscience Research, 2025)
Background: Benign Prostatic Hyperplasia (BPH) and prostate cancer are common prostate-related conditions affecting adult males, especially as they age. Both conditions are associated with various risk factors such as age, family history, smoking, and obesity. Objective: The aim of this study was to investigate the prevalence, risk factors, and diagnostic markers, specifically prostate-specific antigen (PSA) levels, among patients diagnosed with BPH and prostate cancer. Methods: This descriptive cross-sectional study was conducted at Institute of kidney diseases, Hayatabad, Peshawar during June 2022 to March 2023. A total of 125 patients were added in the study. Data for this study were collected through a combination of clinical evaluations, laboratory tests, imaging, and histopathological examinations. Demographic data were collected from each patient, including age, family history of prostate diseases, lifestyle habits, and dietary factors. Results: The prevalence of BPH was found to be significantly higher (64%) compared to prostate cancer (20%). The majority of patients with both conditions were aged 60 years and above. A family history of prostate disease was reported by 50% of prostate cancer patients, while 25% of BPH patients had a similar history. Elevated PSA levels were found in 70% of prostate cancer patients, with a mean PSA of 12.0 ng/mL, compared to 4.5 ng/mL in BPH patients. Smoking and obesity were identified as common lifestyle factors among both patient groups, with prostate cancer patients showing a higher incidence of these risk factors. Conclusions: It is concluded that Benign Prostatic Hyperplasia (BPH) and prostate cancer are prevalent conditions among adult males, with BPH being more common than prostate cancer in this study. Age, family history, smoking, and obesity were identified as significant risk factors for both conditions.